2020
DOI: 10.1016/j.bbmt.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Telehealth Evaluations in Patients Undergoing Hematopoietic Cell Transplantation

Abstract: Telehealth involves the use of telecommunication and information technology for the delivery of clinical care and may be a mechanism to alleviate the burden of visits faced by patients undergoing hematopoietic cell transplantation (HCT). Few studies have evaluated the feasibility and acceptability of telehealth visits in the care of HCT patients. We conducted 27 telehealth visits with 25 patients undergoing HCT using a videoconferencing system that allows for realtime, 2-way interactions and administered satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Our prospective study showed that the use of mobile health care devices and smartphone apps for self-reported outcomes is feasible in the post-HCT setting. In a study conducted by Nawas et al [ 6 ], it was found that telehealth evaluations could be useful in the early peritransplant period, with a high satisfaction rate among patients. In our study, we found that patients felt safer when using the telehealth system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prospective study showed that the use of mobile health care devices and smartphone apps for self-reported outcomes is feasible in the post-HCT setting. In a study conducted by Nawas et al [ 6 ], it was found that telehealth evaluations could be useful in the early peritransplant period, with a high satisfaction rate among patients. In our study, we found that patients felt safer when using the telehealth system.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the quality of telehealth monitoring should be complemented and improved by the collection of other clinically relevant parameters. For example, a virtual physical examination could be carried out through the use of high-quality video calls, digital stethoscopes, and weight scales [ 6 , 7 ]. In our study, the system worked well for detecting acute complications such as infections and dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…This often leads to cases where researchers are defining new measures for specific studies or merging and modifying items from previous questionnaires [20]. In other cases, researchers are relying on single measures of overall satisfaction that do not consider other possible dimensions of the construct [10,21]. This creates a state in telemedicine research where evaluations and comparisons of studies and measures may be difficult.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still concerns are often raised about the lack of attention to the multidimensionality of satisfaction in the telemedicine literature [19]. Yet even recent telemedicine studies still often rely on single measures of overall satisfaction [20]. Although, overall satisfaction may be a good enough indicator for these studies, it is important to consider what is being evaluated and whether measures fit their suggested meaning.…”
Section: Literature Reviewmentioning
confidence: 99%